Tax pressure, farmland management, and agricultural carbon abatement: Empirical evidence from tax-and-fees reform in rural China - Zhang, Xingmin; Wang, Chang’an; Liu, Xiaoqian; Wu, Junqian (Frontiers in Environmental Science, 2022)
Agriculture is the second largest source of carbon emissions in the world. To achieve the strategic goals of "carbon peaking" and "carbon neutrality", how to effectively control agricultural carbon emissions becomes the focus of the Chinese government. As the most critical agricultural policy of China in the early 21st century, assessing the impact of rural tax-and-fees reform on agricultural carbon emissions has powerful theoretical and practical implications. Based on panel data of 31 Chinese provinces from 2000-2019, this paper constructs a continuous difference-in-differences (CDID) model to identify the effects of rural tax-and-fees reform on agricultural carbon emissions, and further tests the mechanisms and heterogeneity for the reform to achieve agricultural carbon emission reduction. The results demonstrate that: (1) The reform can effectively reduce the agricultural carbon intensity and improve the agricultural carbon efficiency, with the effects of -6.35% and 6.14%, respectively. (2) The analysis of dynamic effects shows that the impact of rural tax-and-fees reform on agricultural carbon intensity and carbon efficiency is persistent. (3) Mechanism analysis indicates that the expansion of land operation area, the increase of agricultural productive investment, and the special transfer payment from the central government are one of the effective mechanisms of the reform's carbon reduction effect, which realizes the improvement of agricultural operation efficiency and the reduction of agricultural carbon emissions. However, the impact of tax-and-fees reform on local government revenue is not conducive to the realization of the reform's carbon reduction effect. (4) Heterogeneity analysis illustrates that the reform policy effects differ in natural climatic conditions, topographical conditions and crop cultivation structure. The rural tax-and-fees reform mostly has a significant negative impact on the carbon emissions generated by material inputs and agricultural production. Therefore, to address the climate change crisis and improve the environmental efficiency of agricultural production, it is necessary to reduce peasants' tax burden and also to implement institutional construction efforts.